2017
DOI: 10.1249/mss.0000000000001329
|View full text |Cite
|
Sign up to set email alerts
|

Children with Burn Injury Have Impaired Cardiac Output during Submaximal Exercise

Abstract: Introduction Burn trauma damages resting cardiac function; however, it is currently unknown if the cardiovascular response to exercise is likewise impaired. We tested the hypothesis that, in children, burn injury lowers cardiac output (Q) and stroke volume (SV) during submaximal exercise. Methods Five children with 49±4% total body surface area (BSA) burned (2 female, 11.7±1 y, 40.4±18 kg, 141.1±9 cm) and eight similar non-burned controls (5 female, 12.5±2 y, 58.0±17 kg, 147.3±12 cm) with comparable exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…In addition, something may be difference with children with severe burn injury that are in a hyperadrenergic state. These results are in agreement to are previous work that found attenuated cardiac output during submaximal exercise 16 . Notably, patients with severe burn injury show similar symptoms of heart failure and coronary artery disease, such as exercise intolerance, and resting cardiac dysfunction 34, 35 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, something may be difference with children with severe burn injury that are in a hyperadrenergic state. These results are in agreement to are previous work that found attenuated cardiac output during submaximal exercise 16 . Notably, patients with severe burn injury show similar symptoms of heart failure and coronary artery disease, such as exercise intolerance, and resting cardiac dysfunction 34, 35 .…”
Section: Discussionsupporting
confidence: 94%
“…Given that temperature regulation is disrupted from inadequate core-skin insulation (removal of epidermis, dermis, and subcutaneous tissue) propranolol treatment may increase the risk for heat-related injury by impairing thermoregulation during exercise-heat stress and suppressing cardiac function. Additionally, we have recently shown that cardiac output during submaximal exercise is impaired in severely burned children compared to age matched nonburned children under thermal neutral conditions 16 . Therefore, we designed a study in burned children to determine whether propranolol affects thermoregulatory capacity.…”
Section: Introductionmentioning
confidence: 95%
“…Oxygen uptake and heart rate increase in a linear fashion with exercise intensity. We previously showed that, during submaximal exercise, cardiac output is lower in burned children than nonburned age- and sex-matched children 32 . Additionally, burned children display signs of exercise intolerance and have a lower peak heart rate 32,33 .…”
Section: Discussionmentioning
confidence: 90%
“…We have previously reported that the cardiovascular response to submaximal exercise is diminished in burned children compared with nonburned age-or sex-matched children. 27,28 Thus, burn trauma may have a more pronounced effect in children than adults, and this requires further understanding. Notably, adults have important body morphology characteristics that differ from those of children in early stages of development.…”
Section: Discussionmentioning
confidence: 99%
“…30 Most importantly, Reynolds et al found that, in children, burn injury causes cardiac failure, particularly left ventricular myocardial depression, and that this outcome that was likewise different from that seen in burned adults. 31 We have recently reported that, during submaximal exercise, burned children have exercise intolerance and attenuated peak heart rate values compared with nonburned age-or sex-matched children 27,28 ; however, this type of investigation has not been conducted in burned adults to date. Relative submaximal heart rate (row A) and peak oxygen uptake (row B) during the first three stages of the modified Bruce exercise in men and boys at discharge (pre-training) and after rehabilitation training (post-training) in men and boys.…”
Section: Discussionmentioning
confidence: 99%